Anticryptosporidial action mechanisms of Launaea spinosa extracts in Cryptosporidium parvum experimentally infected mice in relation to its UHPLC-MS metabolite profile and biochemometric tools - Mai M. Elghonemy; Mohamed G. Sharaf El-Din; Dina Aboelsoued; Mohamed F. Abdelhameed; Mohamed A. El-Saied; Nagwa I. Toaleb; Mohamed A. Farag; Abdelsamed I. Elshamy; Abdelbaset M. Elgamal (PLoS ONE, 2025)
Background Cryptosporidium parvum, a leading cause of diarrhea, is responsible for millions of food and waterborne illnesses in humans and animals worldwide. Launaea spinosa (Asteraceae family) is a common herb found in the desert of the Mediterranean region, encompassing the peninsula of Sinai. Traditionally, it has been utilized for managing gastrointestinal issues and inflammation. Methods and findings The present study aimed to assess Launaea spinosa (LS) extracts viz. ethyl acetate (LS-EtOAc), ethanol (LS-EtOH), and n-butanol (LS-BuOH), of different polarities against C. parvum in experimentally infected mice based on immunological, biochemical, histo- and immunohistochemical assays. Extracts were characterized via UHPLC-ESI-LIT-Orbitrap-MS and metabolite profiles were subjected to correlation modeling with bioactivities via supervised Partial Least Square (PLS) to identify active agents. Most L. spinosa extracts reduced fecal C. parvum oocyst count and mucosal burden (P < 0.05) than untreated infected mice, with LS-BuOH (200 mg/kg) exerting the highest reduction percentage (97%). These extracts increased immunoglobulin G (IgG) levels in infected and treated mice at all examined days post treatment. Also, the highest Interferon-Gamma (IFN-γ) and Interleukin-15 (IL-15) levels were obtained after 10 days of post inoculation (dPI), which were restored to a healthy state after 21 days, concurrent with a decrease in Tumor Necrosis Factor-Alpha (TNF-α) (P < 0.001). The increased liver enzyme (alanine aminotransferase, aspartate aminotransferase, and alkaline phosphatase) levels with infection were likewise reduced with extract administration. The LS extracts caused a significant increase in antioxidant glutathione peroxidase (GSH-Px) and catalase (P < 0.001). Examination of colon tissue revealed that infected-treated mice with LS extracts exhibited a reduction in the expression of cleaved caspase-3, damage score, and degenerative changes. Metabolite profiling of different L. spinosa extracts led to the identification of 86 components, primarily phenolic acids, flavonoids, triterpenoid saponins, and fatty acids, with the first report of sulfated triterpenoid saponins in Launaea genus. PLS regression analysis revealed that bioeffects were significantly positioned close to LS-BuOH extract (R2: 0.9) mostly attributed to triterpenoid saponins and flavonoid glycosides. Conclusions This study demonstrated potential anti-cryptosporidial effects of LS extracts, especially LS-BuOH, suggesting its potential for inclusion in future nutraceuticals aimed at C. parvum treatment.